Probiotics to Prevent the Need for, and Augment the Use of, Antibiotics - Gregor Reid (Canadian Journal of Infectious Diseases and Medical Microbiology)
Although humans and microbes are inseparable, our knowledge and understanding of the majority of microbes that help keep us alive and well is in desperate need of further investigation. Of the organisms that influence humans before birth and inhabit various niches from birth to old age, we know little about their identity, origin, metabolic properties, attributes and mechanisms of interactions with the host and surrounding microbes. The use of probiotics ("live microorganisms which when administered in adequate amounts confer a health benefit on the host") has re-emerged as a means to restore and boost the beneficial microbes in our bodies. The timing of resurgent interest in this ancient field coincides with the need to augment or replace antibiotics whose side effects are unwelcome and whose efficacy is diminishing due to drug resistance. Evidence that probiotic strains can act as adjuncts to antibiotic therapy by reducing adverse effects, improving antibiotic function and enhancing mucosal immunity is mounting. It is to our discredit that basic research on microbial ecology has been stalled in Canada for the past 20 years. If supported, research into indigenous and probiotic microbes will form an important part of future research that sheds light on health, disease and a basic understanding of life itself. In some cases, probiotics will be the difference between a good quality of life and a bad one, or perhaps even life over death. Improvements in clinical studies, manufacturing and regulatory standards must coincide with this progress to ensure that physicians and consumers have reliable, proven products for safe and efficacious use.